Interpretation of Familiar Metaphors and Proverbs by Polish People in Middle and Late Adulthood - Szepietowska, Ewa Malgorzata; Filipiak, Sara (International journal of language & communication disorders, 2021)
Background: The ability to understand figurative language, including metaphors and proverbs, decreases with age, although the phenomenon is not universal. Cognitive capacities and education play an important role in the competence connected with figurative language use and comprehension in people during the second half of life. Aims: To identify possible similarities and differences in task performance by subjects representing middle adulthood (40-49 and 50-59 years old) and late adulthood (60-69 and 70-92 years old). Additionally, the analyses took into account factors significantly affecting the results, that is, tasks type (metaphors versus proverbs), the way the answer is given (open-ended versus multiple choice) and types of answers (abstract and concrete). This study also aimed to identify some cognitive correlates of task completion. Methods & Procedures: A total of 86 Caucasian subjects, aged 40-92 years, participated in this study (M[subscript whole group] = 62.37, SD = 15.53); the group included 20 subjects aged 40-49 years (M[subscript age] = 45.4; SD = 3.05), 20 aged 50-59 years (M[subscript age] = 55.50; SD = 2.64), 20 aged 60-69 years (M[subscript age] = 64.40; SD = 2.78), and 26 aged 70-92 years (M[subscript age] = 79.15; SD = 6.27). A total of 20 well-known Polish metaphors and 20 popular Polish proverbs were used to assess the level of proverb and metaphor comprehension. The Montreal Cognitive Assessment Scale and Vocabulary subtest of the Polish version of WAIS-R were applied to assess the cognitive functions. Outcomes & Results: The results of the analyses suggest that there are differences as well as certain similarities between the groups. At 70+ years of age, the ability to explain and comprehend metaphors and proverbs decreases when compared with younger adults. In the 70+ group, the ability to grasp the meaning of both metaphors and proverbs is similar, unlike in the younger groups which present a better ability to explain and comprehend metaphors than proverbs. The conditions related to the types of tasks, that is, spontaneous interpretation and choice of responses, do not affect scores of the oldest subjects. Conclusions: The analysis of response types, that is, abstract versus concrete, shows that, compared with younger groups, people aged 70+ years tend to less frequently provide abstract explanations and more often give concrete (but correct) responses, referring to situational data or examples from everyday life. Moreover, attention, short-term/delayed memory and lexical reserve influence the ability to use and comprehend figurative language to a varied degree.